INSTITUTIONAL FOUNDATIONS FOR DEVELOPING A RISK-BASED CONTROL SYSTEM IN PUBLIC FINANCIAL MANAGEMENT - Javokhir Abdukhakimovich Aripov (Innovate Conferences, 2026)
In the contemporary system of public governance, ensuring the efficient use of financial resources, targeted allocation of budget funds, and maintenance of fiscal discipline constitute core strategic priorities of public financial management. The increasing complexity of economic relations, expansion of government expenditures, diversification of financial operations, and rapid digital transformation necessitate the transition of control mechanisms from traditional ex-post inspection models toward modern institutional arrangements oriented toward risk identification and proactive management. Within this context, the development of a risk-based control system in public financial management represents a strategically significant research direction aimed at improving economic efficiency, preventing financial irregularities, and strengthening institutional trust.